Case Report: Repeated Transcranial Magnetic Stimulation Improves Comorbid Binge Eating Disorder in Two Female Patients With Treatment-Resistant Bipolar Depression - Sciortino, Domenico; Schiena, Giandomenico; Cantù, Filippo; Maggioni, Eleonora; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
Introduction: Binge Eating Disorder (BED) is the most common eating disorder, affecting a large population worldwide; it is characterized by recurrent episodes of binge eating, with no compensatory behaviors. BED is often associated with psychiatric comorbidities, and still represents a challenge in terms of treatment strategies. In the last years, neuromodulation has represented a promising approach in the treatment of BED. We report the cases of two women, affected by Bipolar Disorder Type II (BD-II) and comorbid BED, whose BED symptoms improved after a course of accelerated intermittent Theta Burst Stimulation (iTBS)who sought treatment for a treatment resistant depression. Methods: We decided to administer a course of accelerated intermittent Theta Burst Stimulation (iTBS) as augmentation therapy. We carried out a clinical study, involving neurostimulation on 6 patients with a treatment-resistant depressive episode. The trial consisted of a three-weeks accelerated iTBS treatment, delivered to the left DLPFCdorsolateral prefrontal cortex. Clinical evaluation scales (Hamilton Rating Scale for Depression, Montgomery- Åsberg Depression Rating Scale and Young Mania Rating Scale) were administered at baseline, after two weeks and at the end of the stimulation cycle. Pharmacotherapy was maintained unchanged during the iTBS treatment. Patients gave their informed consent both for the protocol and for the publication. Results: The treatment was well tolerated. Depressive symptoms only slightly improved; however patients’ binge episodes remitted completely, which was a serendipitous finding. BED symptomatology complete remission lasted up to 12 weeks follow-up. Discussion: This is the first study regarding iTBS use in BED in comorbidity with BD-II. Further research is still needed to assess the efficacy of this technique in BED treatment.